The winning game in the major football leagues - Silvestri, R.; Cassese, F. P.; Altavilla, G. (Journal of Human Sport & Exercise, 2019)
The new millennium was marked by the epic of the legendary Barcelona of Guardiola, the coach who revolutionized the world of football with his tiki taka. The search for this game made of fast ball exchanges, continuous changes of position and search for free space to occupy, however, has downgraded what is one of the main technical skills of the game of football, the dribbling. Starting with football schools Pedagogical value of the body and physical activity in childhood. 1vs1 has been set aside to favour other technical fundamentals, so we are in a period where fewer and fewer players take responsibility for trying a game in 1vs1, but prefer to pass the ball to their closest partner. This second study has analysed the scorer rankings of the top 4 European championships (Serie A, Premier League, Spanish League, Bundesliga) of the 2009/2010 and 2017/2018 seasons, taking into account not only the total goals, but also the average shots per game and the average dribbling per game.